Changes of a crystallized look the educators for their students. - Lima, Maria Teresa O. (2014)
This article aims to investigate the conceptions of masculine and feminine gender present in the speech of male and female teachers of an elementary school in the city of São Paulo and analyze the perceptions and the stereotypes present in their speech about their students. To this end, this article investigates and presents the concepts of male and female, presented in the teacher’s speech to characterize men and women, checking how these conceptions appear when the teachers have to point the characteristics of their students. To carry out the research instruments were used to provide a qualitative approach (Likert scale and semi-structured interviews) in order to see in the answers, statements and postures of the different evidences of the way they represent and relate their students on gender issues. The research finds at first, if there are differences in perception of educators on their students related to their gender and which are these differences. Thus, the search finds in the speeches of the educators, the role of the school as an institution forming not only academic knowledge, but also concepts, prejudices, assumptions and values in the students.